Trenching Construction in Peat Soil and the DGGE Analyses of nif Gene and Activity of Dehydrogenase - HAPPY WIDIASTUTI; DARMONO TANIWIRYONO; IMAN RUSMANA; GALUH WENING PERMATASARI (Indonesian Society for microbiology, 2020)
Basal stem rot (BSR) is a major disease in oil palm crops which also possible happen on peat soils. Ganoderma boninense is the pathogen that causes this disease infects the plants through the root. Maintaining root health expects to reduce the intensity of the occurrence of BSR disease and its spread. In this research, trenching construction and maintenance is carried out which aims to break the spread and activity of Ganoderma. Trenching maintenance is carried out by giving empty bunches oil palm inoculated with decomposer, Azotobacter inoculants and humic acid. Four treatments tested were trenched (T1) and untrenched (T0) in combination with two level of Ganoderma attack, which are moderate (Mo) and severe (Se). The soil sample were retrieved from different point, which are in the trenching area (TR), harvest path zone (H), and frond stack zone (M). The soil characteristic including microbe abundance, dehydrogenase activity, and PCR-DGGE of microbe community in each treatment were analyzed to reveal the effect of trenching construction. The results showed that trenching implementation reveals major results related to the abundance of microbes and fungi population, supported by the enhancement of dehydrogenase activity at the block with moderate Ganoderma attack. In addition, the DGGE study effectively separates the microbial population of four separate treatment into two clusters, splitting the grouping depending on the Ganoderma level attack. This study shows enhancement of soil characteristics biologically and nutrients status of oil palm leaves especially P, as the results of trenching construction in peatland. Keywords: peatland; oil palm; trenching, DGGE; microbes